2006
DOI: 10.1161/01.atv.0000219695.84644.56
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the Cholesteryl Ester Transfer Protein Inhibitor Torcetrapib on Apolipoprotein B100 Metabolism in Humans

Abstract: Objective-Cholesteryl ester transfer protein (CETP) inhibition with torcetrapib not only increases high-density lipoprotein cholesterol levels but also significantly reduces plasma triglyceride, low-density lipoprotein (LDL) cholesterol, and apolipoprotein B (apoB) levels. The goal of the present study was to define the kinetic mechanism(s) by which CETP inhibition reduces levels of apoB-containing lipoproteins. Methods and Results-Nineteen subjects, 9 of whom were pretreated with 20 mg atorvastatin, received … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
44
3
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(53 citation statements)
references
References 27 publications
5
44
3
1
Order By: Relevance
“…Moreover, this effect was no longer apparent in people that were treated with torcetrapib in combination with atorvastatin. This is the opposite of what the same authors reported previously, where torcetrapib monotherapy lowered the levels of apoB-100-containing lipoproteins by increasing their fractional catabolic rate ( 20 ). As the samples that Diffenderer and colleagues used in the present study were obtained from the same subjects in which apoB-100 kinetics were investigated ( 20 ), this unexpected observation cannot be attributed to a population effect.…”
contrasting
confidence: 93%
See 2 more Smart Citations
“…Moreover, this effect was no longer apparent in people that were treated with torcetrapib in combination with atorvastatin. This is the opposite of what the same authors reported previously, where torcetrapib monotherapy lowered the levels of apoB-100-containing lipoproteins by increasing their fractional catabolic rate ( 20 ). As the samples that Diffenderer and colleagues used in the present study were obtained from the same subjects in which apoB-100 kinetics were investigated ( 20 ), this unexpected observation cannot be attributed to a population effect.…”
contrasting
confidence: 93%
“…Administration of torcetrapib in combination with atorvastatin also increased the clearance of apoB-100 in VLDL. However, in contrast to what was reported for treatment with torcetrapib alone, administration of torcetrapib in combination with atorvastatin reduced apoB-100 levels by increasing VLDL apoB-100 clearance and by reducing the production of apoB-100 in IDL and LDL ( 20 ).…”
contrasting
confidence: 89%
See 1 more Smart Citation
“…In vivo studies support this model since treatment with a CETP inhibitor was associated with enhanced LDL clearance from plasma, presumably due to upregulation of LDLRs resulting from reduced LDL cholesterol delivery to liver. 110 …”
Section: Cetp Inhibitorsmentioning
confidence: 99%
“…Although the direct effects of CETP inhibition in humans on lipoprotein remnant clearance have not been described, treatment with the CETP-inhibitor torcetrapib has been shown to increase the fractional catabolic rate of both VLDL-apoE ( 49 ) and VLDL-apoB100 ( 50 ). However, the potentially increased catabolism of (V)LDL and thus antiatherogenic properties were clearly not suffi cient to offset or overrule the adverse side effects of torcetrapib.…”
Section: Anacetrapib Decreases (V)ldl-c and Pcsk9 Levels In E3l Micementioning
confidence: 99%